A response of biomass and nutrient allocation to the combined effects of soil nutrient, arbuscular mycorrhizal, and root-knot nematode in cherry tomato - Wang, Lei; Chen, Xin; Yan, Xingfu; Wang, Congli; Guan, Pingting; Tang, Zhanhui (Frontiers in Ecology and Evolution, 2023)
The biomass and nutrient allocation strategies in plants are fundamental for predicting carbon storage and mineral and nutrient cycles in terrestrial ecosystems. However, our knowledge regarding the effects of multiple environmental factors on biomass and nutrient allocation remains limited. Here we manipulated soil composition (three levels), arbuscular mycorrhizal fungi inoculation (AMF, five levels) and root-knot nematode inoculation (RKN, two levels) using random block design to reveal the effects of these factors on biomass and nutrient allocation strategies of cherry tomato. Our results showed that biomass and nutrient allocation were affected by soil composition, AMF and RKN individually or interactively. The biomass and nutrient allocation in cherry tomato shows different adaptation strategies responded to the joint action of three factors. The reduction of soil nutrients increased belowground biomass allocation, and aboveground nitrogen and phosphorus concentration. AMF colonization increased aboveground biomass allocation and reproductive investment and promoted aboveground nitrogen and phosphorus inputs. Cherry tomato can mitigate the stress of RKN infection by investing more biomass and nutrients into belowground organs. Our study showed that plants can adjust their survival strategies by changing biomass and nutrient allocation to adapt to variation in soil abiotic and biotic factors. These findings contribute to our understanding of the adaptive processes of plant biomass and nutrient allocation strategies under multiple environmental factors.